Maternal Knowledge of Umbilical Cord Care and Its Association With Cord Separation Duration: A Cross-Sectional Study in Simalungun Regency - Elv Feedia Mona Saragih; Verawaty Fitrinelda Silaban (Gayaku Publisher, 2026)
Background: The postnatal period is a critical window for newborn survival, during which umbilical cord care directly influences separation timing and infection risk. Postpartum mothers serve as primary caregivers, yet their understanding of appropriate cord care varies considerably based on education, cultural tradition, and access to health information. Objective: This study examined the association between postpartum maternal knowledge of umbilical cord care and cord separation duration among newborns in Raya Kahean District, Simalungun Regency, alongside selected sociodemographic factors. Methods: An observational analytic cross-sectional study was conducted using total sampling of eligible postpartum mothers in the study area. Knowledge was assessed via a structured, validated questionnaire; cord separation duration was determined through direct observation and caregiver report; and associations between categorical variables were tested using the Chi-Square test. Results: Most mothers were of prime reproductive age with junior secondary education, predominantly identifying as homemakers. Cord care knowledge clustered in the moderate category, while most newborns achieved separation within the physiologically expected timeframe. A markedly strong association was found between maternal knowledge and cord separation duration, with better-informed mothers considerably more likely to experience prompt separation. Educational attainment also showed a significant association with separation outcomes, whereas maternal age and occupational status did not. Conclusion: Postpartum maternal knowledge emerged as the dominant determinant of cord separation timing, substantially outweighing age and occupation, while educational background served as a reinforcing structural enabler. These findings highlight the strategic importance of structured, culturally responsive health education within primary care services in this district.